Study on Molecular Recognition between Euphorbia Factor L713283 and β-Tubulin via Molecular Simulation Methods - Shan Chang; Hong-qiu He; Ren Kong; Zhen-jian Xie; Jian-ping Hu (Journal of Chemistry)
Euphorbia factor L713283 is a new lathyrane diterpene isolated from Euphorbia lathyris and shows strong anticancer activity. By using molecular similarity analysis, β-tubulin was identified as one of the possible targets of L713283. We further investigated the binding modes of L713283 with β-tubulin using molecular docking and molecular dynamics (MD) simulation methods. The results indicated that the binding site between β-tubulin and L713283 was composed of the four regions, that is, residues Phe20~Glu27, Leu225~Thr232, Phe270~Gly277, and Ile356~Met363. MM/GBSA method was used to calculate the binding free energy and determine the key residues for the association of L713283 with β-tubulin. It was found that nonpolar interactions made the major contributions for the binding. In addition, we compared the binding pocket and motion modes of L713283-free and L713283-bound β-tubulin systems. It is proposed that L713283 may bind to β-tubulin and favor the formation of αβ-tubulin dimmer. This work provides possible explanation for molecular mechanism of the anticancer agent L713283, and the strategy used here could benefit the investigation of possible target profile for those bioactive agents with unknown mechanisms.